Strategi Komunikasi Word-of-Mouth Religius dalam Ekosistem Pesantren: Telaah Model Pemasaran dari Perspektif Kepercayaan dan Solidaritas Jemaah - Siti Aimah; Mamlukhah Mamlukhah; Hasan Baharun; Fathiyah Mohd Fakhruddin (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2026)
This study identifies a research gap in the consumer behavior literature regarding how spiritual dimensions function to mitigate perceived risk in the decision-making process of selecting Islamic boarding schools, despite the well-established dominance of rational-based models in educational choice. Employing a qualitative case study approach, this research investigates the phenomenon through in-depth interviews, participant observation, and document analysis. The findings reveal that parental decision-making is not purely transactional, but rather shaped by a socio-spiritual trust ecosystem that integrates the charismatic authority of the Kiai with religious word-of-mouth communication. Within this ecosystem, institutional legitimacy is reinforced through culturally embedded practices such as the Haul ritual, a form of collective meaning-making and narrative reinforcement; Sowan, a relational trust-building mechanism; and alumni networks, which function as continuous channels of information diffusion within community-based communication structures. Theoretically, this study contributes to the service marketing and consumer behavior literature by extending the concept of trust formation by introducing spiritually mediated loyalty into educational decision-making contexts, thereby broadening the explanatory capacity of existing rational-choice frameworks. On a broader level, the study contributes to global discourse on community-based education marketing in developing and collectivist societies. In practice, the findings suggest that Islamic boarding school management should strengthen institutional trust by reinforcing leadership credibility, spiritual authenticity, and community-based relational networks, rather than relying primarily on physical infrastructure.